Del Padre y la función paterna...en la homosexualidad femenina - Hebe Celina Gioiosa (Affectio Societatis, 2014)
Psychoanalysis and culture show in their intimacy the knotting of issues relating to desire and jouissance via love. The encounter with contemporary problems —such as homosexuality and the desire to be parents— will require an analysis beyond our field by linking the legal and the social. From the psychoanalytic framework, it will be interesting to present a thorough study in the interest of specifying the paternal function in order to consider the feasibility of its operation. This paper is part of an ongoing thesis that invites to think about the issues here referred in the context of Lacanian psychoanalysis.